2012
DOI: 10.1186/1746-6148-8-163
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and economic burden of un-owned cats and dogs in the UK: results of a 2010 census

Abstract: BackgroundThe population of dogs and cats passing through rescue shelters may be subject to compromised welfare and increased susceptibility to disease. Little information exists to describe this population, its dynamics and associated management practices. The aim of this study was to carry out a census of un-owned cats and dogs in the UK in 2010, and to document the origins, destinations, husbandry and costs associated with the care of these animals.ResultsA sampling frame was constructed by searching the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
77
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 26 publications
1
77
0
3
Order By: Relevance
“…Despite the popularity of cat and dog ownership, many UK animal welfare organisations report that they are continually full with long waiting lists (Clark and others 2012, Stavisky and others 2012). The pressure for places at rehoming centres results from factors including owner relinquishments and a shortage of available households willing to offer these unwanted pets a home.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the popularity of cat and dog ownership, many UK animal welfare organisations report that they are continually full with long waiting lists (Clark and others 2012, Stavisky and others 2012). The pressure for places at rehoming centres results from factors including owner relinquishments and a shortage of available households willing to offer these unwanted pets a home.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that targeting this risk factor, for example, through improved owner education, could lead to the biggest impact on reducing the number of unplanned litters that are produced. The estimate of approximately 850,000 unplanned kitten births that could be prevented each year (by removing this belief within the cat-owning population) represents more than six times the annual number of cats and kittens that enter animal welfare organisations each year (Clark and others 2012, Stavisky and others 2012), and thus highlights the potential difference that could be made by addressing this commonly held belief among cat owners that female cats should have a litter before being neutered.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the higher C. felis prevalence in stray cats than in pet cats. One study reported that a large number of cats and dogs become unowned each year in the UK, which may have considerable implications for their welfare [21]. …”
Section: Discussionmentioning
confidence: 99%